When Trump Tariffs Shake the World: Are Indonesian Sharia Stocks Shockproof? - Fuad Hasyim; Maksum; Nur Hidayat (Journal of Islamic Economics Perspectives, 2025)
This study investigates the resilience of the Indonesia Sharia Stock Index (ISSI) to policy-induced ambiguity shocks, with a specific focus on Trump tariff policies framed within the VUCA paradigm. Employing a GARCH-X(1,1) model on daily data spanning from 3 June 2024 to 27 June 2025, the findings reveal that ISSI exhibits greater sensitivity to global uncertainty, significantly influenced by the VXEEM index than the conventional Jakarta Composite Index (IHSG). However, the dummy variable representing Trump’s tariffs shows no statistically significant impact on the volatility of either market. These results suggest that the ethical screening mechanisms underlying Sharia-compliant stocks may offer limited protection against non-systemic, policy-driven shocks. The study offers conceptual and methodological contributions to the discourse on Islamic finance volatility modeling in an increasingly ambiguous global policy environment.